SEGMENTASI POTENSI DAERAH WISATA DI KOTA BIMA MENGGUNAKAN K-MEANS - Yanuar Wicaksono (Informatika Publisher, 2021)
The city of Bima is also located between the islands of Bali, Lombok and Labuan Bajo, which have tourist destinations that are in great demand by both domestic and foreign tourists, so that the city of Bima has potential as a tourist destination. The total number of tourist visits experienced a decline from the number of visits from 2019 of 56.39%, which from BPS data the number of tourist visits in 2019 was 170,646 people. During the pandemic, finding the right target in addition to segmenting the market from tourists, managers can identify a market with purchasing power, geographic location, facilities that are already available at tourist objects. By using K-means, it is hoped that the segmentation of the potential of tourist areas in the City of Bima can produce recommendations for the City Government of Bima to develop a strategy for developing tourist destinations. In developing tourism potential, institutions are strengthened through village/kelurahan tourism. For the Districts of Raba and Mpunda even though they are far from Teluk Bima, which do not have marine tourism, they can develop other types of tourism objects such as culinary tourism. The need for travel agents in the promotion of tourist destinations needs to be increased inversely with the number of guides, because the guides will be maximized if the tourists visiting are directly proportional to the number of guides.